Early universe cosmology and its observational effects on the cosmic microwave background - Charnock, Tom (2017)
This Thesis is written in three parts. The first part describes the analytic calculation of the unequal-time correlator of cosmic strings and superstrings. The first efficient constraint analysis of all string and superstring network parameters is performed. By studying the effect of cosmic strings on the cosmic microwave background (CMB) radiation it is discovered that cosmic strings must make up a vanishingly small proportion of the energy density of the universe. The constraints on string network parameters are all skewed toward reducing the magnitude of energy density arising from strings. Also in this Part, a better comprehension of the unconnected segment model (USM) was gained. In particular, a greater understanding of the string scaling parameter $L_f$ was garnered, as well as finding the reason why the USM tends to provide greater power than simulations of Nambu-Goto cosmic strings.